The Impact of Preexisting Illness and Substance Use on Functional and Neuropsychological Outcomes Following Traumatic Brain Injury. Issue 3 (1st July 2016) - Dahdah, Marie N.; Barnes, Sunni A.; Buros, Amy; Allmon, Andrew; Dubiel, Bs, Rosemary; Dunklin, Cynthia; Callender, Librada; Shafi, Shahid
Abstract : Traumatic brain injury (TBI) is a significant public health problem in the US. Specific preexisting medical illnesses delay recovery after TBI and increase mortality or risk of repeat TBI. This study examined the impact of preexisting illness and substance use on patient rehabilitation outcomes following TBI. The Functional Independence Measure total score and Disability Rating Scale score measured functional outcomes at discharge from inpatient rehabilitation, while the Trail Making Test A and B and Total Trials 1-5 of the California Verbal Learning Test-II measured neuropsychological outcomes in 128 TBI survivors with moderate or severe TBI. Results showed that the presence of a heart condition or diabetes/high blood sugar was associated with lower functional outcomes by discharge. A history of a heart condition, stroke, or respiratory condition prior to TBI was associated with reduced cognitive flexibility. Those with preexisting diabetes/high blood sugar demonstrated poorer visual attention, visuomotor processing speed, and ability to learn and recall verbal information. Those with pre-TBI cancer also had greater auditory-verbal memory deficits. The findings showed that specific preexisting medical conditions are independently associated with lower functional and cognitive outcomes for patients with TBI. By screening patients for preexisting medical conditions, multidisciplinary TBI rehabilitation teams can identify patients who require more aggressive treatments or greater length of stay.